Geração de energia elétrica excedente no setor sucroalcooleiro: entraves estruturais e custos de transação - Souza, Zilmar José de (2003)
Given the estimated potential of electric energy generation around 18 thousand MW and the necessity to expand and diversify the installed national capacity of energy generation, this dissertation investigates the reasons for the low performance in the exploitation of the investment opportunities in electric energy commercialization by the sugarcane sector. With this purpose, the research presents a diagnosis of the main structural obstacles and transaction costs present in the generation of electric energy surpluses, showing the importance of the institutions in the decision of expansion of the activity by the sugarcane sector. The results were contrasted with the proposal of governmental energy policy for incentive this activity. It was verified the necessity of improvement in the current institutional environment. The main contribution of the dissertation was to present directives to public policies. These directives focus the financing for the expansion of the activity; the commercialization of the excesses; the tax incentive; and the concession of direct subsidies to the expansion of the activity. The directives related to financing were: official lines differentiated by technology use, index of mechanization and scale; the Ethical Fund Formation for the sector; and projects finance involving Emissions Reduction Certificate. Regarding commercialization, directives were: subvention to the transport tariffs; the extension of the universe of potentially free consumers; formation of trading pools and inclusion in the Energy Replacement Mechanism; the insertion of the sugarcane energy in the composition of Factor X and in the National Energy Reserve; changes in the retailers' auto-supplement; and incentive to the commercialization of energy surpluses and of Emissions Reduction Certificates. Directives related to tax incentive were also presented. Regarding direct subsidies, it is interesting the use of the resources that come from the Use of Public Good and Fuel Consume Account to foster the expansion of the energy surpluses commercialization.